Anaemia in pregnancy: a retrospevtive study in maternal child and health clinic Sri Aman, Sarawak - Dayangku Siti Rafidah, Pengiran Hashim (Universiti Malaysia Sarawak (UNIMAS), 2011)
This is a retrospective study on anaemia in pregnancy of 250 respondents who went for antenatal follow up in MCHC Sri Arnan and delivered in 2010. Sri Aman, a rural area which recorded high prevalence of anaemia compared to other divisions in Sarawak. The purpose of this study are to study the prevalence of anaemia and its relation to sociodemographic characteristics, obstetric profile and birth outcome. Antenatal index cards were used to calculate the prevalence using WHO criteria of anaemia (Hb<llg1dl). Data obtained were compared according to categories whereby anaemia status was the dependent variable The results showed those less than 20 years old, minority ethnicity, educated at primary or lower level, skilled workers and not married had the highest prevalence of anaemia. Further analysis showed that, age, level of education, occupation and marital status do not have significant association with anaemia. In term of obstetric profile, higher prevalence of anaemia was observed in respondents with positive history of abortion, anaemia for past pregnancy and no history of Caesar. Users of oral contraceptive pills seem to have lower anaemia prevalence. Its significance was unable to be calculated . I ~ as data was too small. Longer spacing, grandmultigravida and primiparity had the highest prevalence of anaemia but were found insignificant. Mean birth weight of newborns of these respondents was 3.0 kg (±0.41). Low birth weight constitutes 9.2% of study. Highest anaemia prevalence was among mothers of macrosomic babies but sample size was too small to be analysed. Fisher exact test analysis showed no significant association of birth xi weight of babies and anaemia status of mothers. It is recommended for future study, findings in this study can be more meaningful if bigger sample size could be obtained.